Biomechanical evaluation of the reconstruction of the calcar femorale in femoral neck fractures: a comparative finite element analysis - Zhihao Gao; Jianxiong Ma; Ying Wang; Bin Lu; Haohao Bai; Lei Sun; Hongzhen Jin; Zijian Zhang; Xinlong Ma (Journal of International Medical Research, 2022)
Objective Femoral neck fractures are common. We evaluated the biomechanical performance of an internal fixation method based on traditional three cannulated screws (3CS) inserted from below the fracture in the direction of the calcar femorale in the treatment of Pauwels III femoral neck fracture. Methods We constructed and evaluated a three-dimensional model of a Pauwels III femoral neck fracture with four models of internal fixation (3CS, and 150°, 155°, and 160° nailing angles) for reconstruction of the calcar femorale, by finite element analysis (FEA). Results The peak stress values at the fracture ends in the 3CS, 150°, 155°, and 160° nailing angle models were 30.052 MPa, 33.382 MPa, 34.012 MPa, and 29.858 MPa; peak stress values for internal fixed stress were 315.121 MPa, 228.819 MPa, 198.173 MPa, and 208.798 MPa; and the maximum displacement of the femoral head was 13.190 mm, 13.183 mm, 12.443 mm, and 12.896 mm, respectively. Conclusion FEA showed that the new nailing methods and the 160° nailing angle for reconstruction of the calcar femorale showed better performance in resisting shearing force for Pauwels III femoral neck fracture, with better mechanical properties, than those with the other three models. These findings can provide a clinical reference.